204k views
5 votes
Solve the system of equations y=4x+1, y=x2+2x-2

User Usama Ejaz
by
5.7k points

2 Answers

6 votes
Option d is the answer to your question
User Lifeisstillgood
by
4.9k points
2 votes
option D
(-1,-3) and (3,13)

Given in the question two equations
y = 4x + 1
y = x² + 2x - 2
Equate both functions
4x + 1 = x² + 2x - 2
rearrange the x term and constant
-x² + 4x - 2x + 2 + 1 = 0
-x² + 2x + 3 = 0
factors
-x * 3x = -3x²
-x + 3x = 2x
-x² -x + 3x + 3 = 0
-x(x+1) +3(x+1) = 0
solve
(x+1)(3-x) = 0
x = -1
and
x = 3
Plug these values in equation to find y
x = -1
y = 4(-1)+ 1
y = -3
x = 3
y = 4(3)+ 1
y = 13
User Ecv
by
6.0k points
Welcome to QAmmunity.org, where you can ask questions and receive answers from other members of our community.